Endovascular Treatment With or Without Prior Intravenous Alteplase for Acute Ischemic Stroke. Issue 11 (4th June 2019) - Chalos, Vicky; LeCouffe, Natalie E.; Uyttenboogaart, Maarten; Lingsma, Hester F.; Mulder, Maxim J. H. L.; Venema, Esmee; Treurniet, Kilian M.; Eshghi, Omid; van der Worp, H. Bart; van der Lugt, Aad; Roos, Yvo B. W. E. M.; Majoie, Charles B. L. M.; et al.
Abstract : Background: It is unclear whether intravenous thrombolysis (IVT) with alteplase before endovascular treatment (EVT) is beneficial for patients with acute ischemic stroke caused by a large vessel occlusion. We compared clinical and procedural outcomes, safety, and workflow between patients treated with both IVT and EVT and those treated with EVT alone in routine clinical practice. Methods and Results: Using multivariable regression, we evaluated the association of IVT+EVT with 90‐day functional outcome (modified Rankin Scale), mortality, reperfusion, first‐pass effect, and symptomatic intracranial hemorrhage in the MR CLEAN (Multicenter Randomised Controlled Trial of Endovascular Treatment for Acute Ischemic Stroke in The Netherlands) Registry. Of 1485 patients, 1161 (78%) were treated with IVT+EVT, and 324 (22%) with EVT alone. Patients treated with IVT+EVT had atrial fibrillation less often (16% versus 44%) and had better pre‐stroke modified Rankin Scale scores (pre‐stroke modified Rankin Scale 0: 73% versus 52%) than those treated with EVT alone. Procedure time was shorter in the IVT+EVT group (median 62 versus 68 minutes). Nontransferred IVT+EVT patients had longer door‐to‐groin‐puncture times (median 105 versus 94 minutes). IVT+EVT was associated with better functional outcome (adjusted common odds ratio 1.47; 95% CI: 1.10–1.96) and lower mortality (adjusted odds ratio 0.58; 95% CI: 0.40–0.82). Successful reperfusion, first‐pass effect, and symptomatic intracranial hemorrhage did not differ between groups. Conclusions: In this observational study, patients treated with IVT+EVT had better clinical outcomes than patients who received EVT alone. This finding may demonstrate a true benefit of IVT before EVT, but its interpretation is hampered by the possibility of residual confounding and selection bias. Randomized trials are required to properly assess the effect of IVT before EVT.